2019
DOI: 10.25073/2588-1116/vnupam.4186
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development and Social, Ecological, and Economic Transformation in Vietnam: Insights for Policy

Abstract: Vietnam is at crossroads: being a middle income country now, it has to deal with social, economic and environmental challenges better known from affluent countries, while still being in the transition from an agricultural to an industrial in a society transiting from rural to urban. At the same time, Vietnam has to prepare for the diverse impacts of climate change, a process beyond its control, by developing adaptation measures safeguarding the social and environmental basis of the society and economy. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The Mekong Delta is currently facing major challenges in terms of climate change and upstream dams and current food production systems should be designed so they contribute to an increased resilience and a sustained production of food (Vietnamese Government 2017 , 2020 ; Spangenberg 2019 ; Hui et al 2022 ). The Delta is at cross roads where future farming strategies either could focus on an intensified production of rice through increased input of external resources, such as more agriculture chemicals, in an increasingly human controlled environment, or build on a diversified production of rice and other crops, with the aim to increase the efficiency use and recycling of resources rather than a throughput of external resources.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Mekong Delta is currently facing major challenges in terms of climate change and upstream dams and current food production systems should be designed so they contribute to an increased resilience and a sustained production of food (Vietnamese Government 2017 , 2020 ; Spangenberg 2019 ; Hui et al 2022 ). The Delta is at cross roads where future farming strategies either could focus on an intensified production of rice through increased input of external resources, such as more agriculture chemicals, in an increasingly human controlled environment, or build on a diversified production of rice and other crops, with the aim to increase the efficiency use and recycling of resources rather than a throughput of external resources.…”
Section: Discussionmentioning
confidence: 99%
“…This has increased income and food security but has also been followed by negative environmental impacts, such as pollution and biodiversity change (Tong 2017 ; Sebesvari et al 2012 ; Nguyen et al 2019 ; Spangenberg 2019 ). Tam et al ( 2016 ) reported that farmers spraying organophosphates on rice fields resulted in both reduced growth and survival rates of fish and Dasgupta et al ( 2007 ) found that over 35% of 190 rice farmers in the Mekong Delta, experienced acute pesticide poisoning.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the agricultural sector, women hold an undeniable and crucial role (Anderson et al, 2021), making up 43% of the labor force in developing countries, as noted by Patil et al (2018). In Vietnam, the primary source of sustainable livelihood for the majority of the population is farming and various agricultural pursuits (Spangenberg, 2019).…”
Section: Introductionmentioning
confidence: 99%